2020
DOI: 10.1002/adem.202000112
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ligand Treatment on the Tuning of Infrared Plasmonic Indium Tin Oxide Nanocrystal Electrochromic Devices

Abstract: Electrochromic devices operating in the near infrared are being developed as a part of smart windows that can dynamically modulate visible light and heat transmittance of solar irradiation, dependent on weather conditions and personal preferences. Here, doped metal oxide nanocrystals are used to obtain the desired effect in the infrared spectral region. Specifically, the infrared transmittance is electrochemically modulated by control of the carrier concentration in the nanocrystals. While indium tin oxide nan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…Because of its high transparency and conductivity [1,2], ITO is an important electrode material in electrochemical studies and applications that take benefit of its transparent optical and electronic conductive properties [3]. It has been used in different applications or research developments related to photovoltaics [4], electrochromism [5,6], fuel cells [7], electrocatalytic devices [8,9]. Its combined optoelectronic properties makes ITO substrate an electrode material of choice allowing complementary optical or spectroscopic inspection during electrochemical processes for mechanistic or electroanalytical, or sensing [10] studies.…”
Section: Introductionmentioning
confidence: 99%
“…Because of its high transparency and conductivity [1,2], ITO is an important electrode material in electrochemical studies and applications that take benefit of its transparent optical and electronic conductive properties [3]. It has been used in different applications or research developments related to photovoltaics [4], electrochromism [5,6], fuel cells [7], electrocatalytic devices [8,9]. Its combined optoelectronic properties makes ITO substrate an electrode material of choice allowing complementary optical or spectroscopic inspection during electrochemical processes for mechanistic or electroanalytical, or sensing [10] studies.…”
Section: Introductionmentioning
confidence: 99%
“…It is found that the development of smart windows with various switchable states including transparent, dimmed, cold and hot is possible with the use of this material. In this nanocomposite, the heat radiation transmittance can be controlled by ITO nanocrystals that exhibit an extensively tunable localized surface plasmon resonance [69]. It is also reported that the infrared transmittance is electrochemically controlled by the carrier concentration of ITO nanocrystals [69].…”
Section: Infrared Reflective and Electrochromic Coatingsmentioning
confidence: 92%
“…[43,44] While the latter one, electrochromism, describes a phenomenon where applying an external field will give rise to optical change like evolution, loss, or variation of the materials' color. [45][46][47][48][49][50][51][52][53][54][55][56][57] Low-dimensional materials such as graphene, [48] transition metal oxides, [45] and metal oxide nanocrystals [49] gradually become the alternative electrochromic (EC) materials to replace conventional ones in consideration of fabrication costs. Their high surface area, fast switching time, and good chemical stability characteristics make them good candidates in the electrochromic devices.…”
Section: Introductionmentioning
confidence: 99%